Propuesta de indicadores para promover los emprendimientos turísticos sostenibles del destino Puerto López - Gómez Mejía, Diana Selena (2023)
The purpose of this research was to propose sustainability indicators to promote tourism enterprises in the destination of Puerto López, for this purpose, an exploratory and descriptive, non-experimental research was established. The work consisted of three phases; in phase 1, the destination was characterised, the ventures were categorised and the economic, social and environmental aspects of a sample of 55 tourism ventures were evaluated, and the SWOT, EFE and EFI matrices were used to determine the external and internal factors that affect tourism ventures. In phase 2, the tourist's perception of the ventures was measured by applying a questionnaire to 194 tourists, using stakeholder matrices to determine the management carried out by the entities focused on the development of tourism ventures. In phase 3, the indicators were proposed and validated using a focus group technique, and finally it was proposed to whom they were addressed for their subsequent use. It became evident that the destination of Puerto López, despite its wealth of tourism activities, needs to improve the environmental, social and economic management of tourism enterprises, as these form part of the economic dynamisation of the canton. In effect, a total of 30 indicators were validated, of which 12 are linked to the social dimension, 6 to the economic dimension and 12 to the environmental dimension. In conclusion, these indicators were adapted to be applied in measuring the sustainability of tourism enterprises in the canton of Puerto López through the local government and NGOs.